Bio Lubricant Production Over Modified Alkaline Catalyst from Waste Pome - Ravi, Divin Kumar (2023)
This research focuses on repurposing Palm Oil Mill Effluent (POME) from Malaysia's palm oil industry, aiming to mitigate its environmental impact by converting it into valuable bio lubricants.